Comparative assessments of myocardial iron load in thalassemia patients between dark blood and bright blood MRI T2* techniques - Jixing Yi; Min Wu; Suzhen Wei; Qiliang Huang; Bumin Liang; Peng Peng; Tao Li; Fengming Xu (Frontiers in Medicine)
ObjectiveTo investigate the difference of black blood (DB) and bright blood (BB) T2* techniques at 1.5 T and 3 T in the assessment of myocardial iron load in patients with thalassemia (TM).MethodsAs a retrospective study. CMRtools software was used to measure myocardial T2* in 359 patients with moderate (60 g/L < Hemoglobin<90 g/L) or severe (Hemoglobin<60 g/L) thalassemia. A truncation method was used to remove signal values that deviated from the fitted curve. T2* (DBx-T2*, BBx-T2*) containing all (eight echoes) signals (DB8-T2*, BB8-T2*) and the optimal signal (coefficient of determination R2 > 0.95) were recorded. The difference, correlation and consistency of T2* measured by different methods were compared.ResultsThere was no significant difference (p > 0.05) in myocardial T2* measured by different methods (1.5 T, 3 T), and all of them were highly positively correlated (p < 0.05, rs > 0.9). Bland–Altman analysis showed that (1.5 T) DB8-T2* and DBx-T2*, DBx-T2* and BBx-T2* had good consistency (p > 0.05). (3 T) DB8-T2* and DBx-T2* had good consistency (p > 0.05). There were proportional differences in T2* values measured by the other methods (p < 0.05), and none of them could be considered to have good consistency.ConclusionDB CMR T2* and BB CMR T2* can be interchangeable in the assessment of myocardial iron load in TM patients. However, DB CMR T2* is more stable and reliable.